Pharmacokinetics of recombinant factor XIII in young children with congenital FXIII deficiency and comparison with older patients. (9th July 2013) - Williams, M.; Will, A.; Stenmo, C.; Rosholm, A.; Tehranchi, R.
Summary Congenital factor XIII (FXIII) deficiency is a rare bleeding disorder, which in its severe form is associated with a significant bleeding phenotype, requiring regular prophylactic therapy. A recently developed recombinant FXIII (rFXIII) has demonstrated safety and efficacy in children aged ≥6 years and adults (mentor™1 trial). This article describes the mentor™4 trial, which has assessed the pharmacokinetics (PK) and safety of rFXIII in younger children (1 to <6 years) with congenital FXIII deficiency, and compares extrapolated PK parameters with the mentor™1 trial. Six children with congenital FXIII A‐subunit deficiency received a single, 35 IU kg−1 rFXIII dose. PK properties were similar in all the children, with a mean area under the concentration vs. 30‐day time curve of 248.6 IU h−1 mL−1, maximal FXIII activity (30 min) of 0.67 IU mL−1, and mean 30‐day trough of 0.21 IU mL−1. All patients maintained FXIII activity above the lower target level (0.1 IU mL−1). rFXIII half‐life was 15.1 days (range, 10–25). No safety findings of clinical concern were observed. PK properties of rFXIII were similar in patients from both trials. The study demonstrated that a single dose of 35 IU kg−1 rFXIII maintained plasma FXIII levels above 0.1 IU mL−1 over a 30‐day period in young children with congenital FXIII deficiency, and is, therefore, likely to provide adequate prophylaxis in this age group. The study extends the previous findings of the mentor™1 trial and confirms that no dose adjustment is required for different age groups with congenital FXIII deficiency.